Vilhelm Beck: - omstridt gennem 133 år - Aage, Hans (Kirkehistoriske Samlinger, 2002)
During 40 years, from 1861 to his death in 1901, Vilhelm Beck was the undisputed leader and mentor of Kirkelig Forening for den indre Mission i Danmark (the Home Mission, an evangelical branch of the Church of Denmark). From modest beginnings Indre Mission under his leadership developed into an influential revival movement, which at the turn of the century had 150 full-time employed missionaries and 400 meeting-houses and also included schools, high-schools, hotels, youth organizations, publishing firms etc. Vilhelm Beck was a highly diligent and talented leader. His extremely powerful preaching gathered large crowds beneath his pulpit, in churches, in meeting-houses and in the open, and he was widely admired for his eloquence and humour. Still, he was controversial and earnest and also widely criticised. No less than three derogatory biographies have appeared over a span of 133 years, by Worm (1868), by Aakjær (1897) and by Clausen (2001), besides several publications by his admirers and an autobiography (1901). At present the more disparaging view prevails as represented by the recent biography by Clausen (2001), who explains Vilhelm Beck’s impressive endeavours as driven by suppressed sexuality, avarice and first of all an insatiable lust for power. On the basis of well-known primary sources as well as secondary material this essay argues that this view is undocumented and distorted, and it also offers, mostly by means of selected, illustrative quotations and examples, a more balanced impression of this great man and his life work.